Educational Marketing Strategy in Increasing Competitiveness (Comparative Study of Darul Musyawirien and Al-Barkah Sapeken Sumenep Islamic Boarding Schools 2025) - Ibrahim Al-Khalil; Moh. Hamzah (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
Competition between Islamic educational institutions, particularly Islamic boarding schools in the archipelago, demands an effective educational marketing strategy to increase competitiveness. The educational marketing mix (product, price, place, promotion, people, process, and physical evidence) is a strategic approach to attract public interest and improve service quality. Darul Musyawirien Islamic Boarding School and Al-Barkah Islamic Boarding School in Pagerungan Kecil, Sapeken, Sumenep have different characteristics, strategies, and challenges in their implementation. This study aims to analyze the implementation of the marketing mix strategy in both Islamic boarding schools, identify strengths and weaknesses, and examine supporting and inhibiting factors in increasing competitiveness in the archipelago. The study uses a qualitative approach with a comparative study method through interviews, observation, and documentation, and is analyzed using an interactive analysis model that includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that Darul Musyawirien Islamic Boarding School excels in service innovation, student skill development, and the use of educational technology, while Al-Barkah Islamic Boarding School excels in its religious positioning as a tahfidz Islamic boarding school and its affordable tuition fees, thus having high social appeal. Both Islamic boarding schools face obstacles in the form of limited technological infrastructure, facilities, and geographical conditions. Therefore, a simple social media-based digital strategy is needed, strengthening alumni networks and partnerships, and adaptive hybrid learning to increase the effectiveness of the marketing mix and sustainable competitiveness.